Strategi Promosi Wisata Kemuseuman di Media Sosial - Ariq Zaidan; Doddy Iskandar C (Bandung Conference Series: Public Relations, 2024)
Abstract. The Geology Museum utilizes Instagram social media as an information and promotional medium with the Instagram account name @museum_geologi which is used as a dissemination of information related to the activities carried out by the Geology Museum. In an effort to carry out promotions with education related to geology on the Instagram account @museum_geologi create various content related to geology and archeology. the researcher intends to further analyze how the museum tourism promotion strategy is carried out by the Geology Museum through Instagram social media @museum_geologi. This study uses a qualitative research method with a case approach, and uses a constructivism paradigm. Sources of data obtained through observation, interviews, and documentation in the field. Data analysis that researchers use is technical analysis of data reduction, data presentation, and drawing conclusions. The results of this study are 1.) The promotion strategy carried out by the Geology Museum uses the social media Instagram @museum_geologi by posting content that highlights the advantages of the collections in the Geology Museum and posting posters of activities or events that will take place at the Geology Museum such as Day and Night at Museum and Freedom of learning. 2) Innovations made by the Geology Museum on the Instagram account @museum_geologi by making various posts by posting photos, video reels and less formal content such as Tiktok. Apart from that, by making the characterization of someone who makes the icon of the Geology Museum. 3) The reason for the Geology Museum using Instagram as a media promotion strategy is because the use of Instagram by the Geology Museum costs not too much, ease of operation is also flexible and can be used anywhere. 4) Obstacles that occur at the Geology Museum when implementing a tourism promotion strategy on the Instagram account @museum_geologi are caused by internal and external factors. Abstrak. Museum Geologi memanfaatkan media sosial Instagram sebagai media informasi dan promosi dengan nama akun Instagram @museum_geologi yang digunakan sebagai penyebaran informasi berkaitan dengan kegiatan yang dilakukan Museum Geologi. Dalam upaya melakukan promosi dengan edukasi yang berkaitan dengan geologi pada akun Instagram @museum_geologi membuat berbagai konten yang berkaitan dengan geologi dan arkeologi. peneliti bermaksud menganalisis lebih jauh bagaimana strategi promosi wisata kemuseuman yang dilakukan Museum Geologi melalui media sosial Instagram @museum_geologi. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan kasus, dan menggunakan paradigma konstruktivisme. Sumber data yang diperoleh melalui observasi, wawancara, serta dokumentasi di lapangan. Analisis data yang peneliti gunakan ialah teknis analisis reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini adalah 1.) Strategi promosi yang dilakukan oleh Museum Geologi menggunakan media sosial Instagram @museum_geologi dengan memposting konten yang menonjolkan keunggulan koleksi yang ada di Museum Geologi dan memposting poster kegiatan atau event yang akan berlangsung di Museum Geologi seperti Day and Night at Museum dan Merdeka belajar. 2) Inovasi yang dilakukan Museum Geologi pada akun Instagram @museum_geologi dengan melakukan variatif postingan dengan memposting foto, video reels dan konten-konten tidak terlalu formal seperti Tiktok. Selain itu dengan membuat penokohan seseorang yang menjadikan ikon Museum Geologi. 3) Alasan Museum Geologi menggunakan Instagram sebagai media strategi promosi karena penggunaan Instagram oleh Museum Geologi dengan biaya yang dikeluarkan tidak terlalu banyak, kemudahan dalam pengoperasian juga fleksibel bisa digunakan dimana saja. 4) Hambatan yang terjadi pada Museum Geologi saat melakukan strategi promosi wisata pada akun Instagram @museum_geologi diakibatkan faktor internal dan eskternal.